2022
DOI: 10.1007/s12161-022-02235-0
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Efficient Loop-mediated Isothermal Amplification (LAMP) Assay for the Authentication of Food Supplements Based on Maitake (Grifola Frondosa)

Abstract: Grifola frondosa (“Maitake”) is an edible fungus with several nutraceutical properties, largely used in traditional medicine. The increased use of Maitake as a food supplements ingredient raised the need of accurate authentication methods since the morphological identification of G. frondosa is not feasible in formulated food supplements. We developed a diagnostic tool based on loop-mediated isothermal AMPlification (LAMP) for the detection of G. frondosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These results suggest that the putative matrix effect of components present in bark extract does not decrease the sensitivity of the LAMP assay at 40 pg or higher of DNA. Other studies have shown sufficient tolerance of LAMP assays to potential inhibitors present in host extract (Fochi et al, 2022; Kaneko et al, 2007), making it an efficient detection method without the need for lab‐based DNA purification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the putative matrix effect of components present in bark extract does not decrease the sensitivity of the LAMP assay at 40 pg or higher of DNA. Other studies have shown sufficient tolerance of LAMP assays to potential inhibitors present in host extract (Fochi et al, 2022; Kaneko et al, 2007), making it an efficient detection method without the need for lab‐based DNA purification.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown sufficient tolerance of LAMP assays to potential inhibitors present in host extract (Fochi et al, 2022;Kaneko et al, 2007), making it an efficient detection method without the need for lab-based DNA purification.…”
Section: Discussionmentioning
confidence: 99%
“…( Sasaki and Nagumo, 2007 ; Chaudhary et al, 2012 ; Li et al, 2013 ; Chaudhary and Khan, 2014 ; Lai et al, 2015 ). While Zhao et al (2016) developed ITS2-specific LAMP primers targeting Crocus sativus L. (saffron) to enable simple and sensitive differentiation from adulterants, Fochi et al (2022) developed a LAMP-based diagnostic protocol for the authentication of food supplements made from the edible fungus Grifola frondosa (Dicks.) Gray (“Maitake”).…”
Section: Current Developments and Horizon Scanmentioning
confidence: 99%